Skrining Fitokimia Sediaan Infusa Kombinasi Daun Ciplukan, Bunga Kamilen dan Daun Stevia - Sriwidyawati A. Solong; Reni Ariastuti; Khotimatul Khusna (STIKes Ibnu Sina Ajibarang, 2024)
Ciplukan leaves, kamilen flowers, and stevia leaves are widely used herbal plants known for their pharmacological activities, which are mainly attributed to the presence of secondary metabolite compounds. These compounds play an important role in providing therapeutic effects such as antioxidant, anti-inflammatory, and antimicrobial properties. One approach to enhancing the effectiveness of these plants is by combining them into a single preparation. This study aims to identify the content of secondary metabolite compounds in a combined infusion (infusa) of ciplukan leaves, kamilen flowers, and stevia leaves. The research method used is a laboratory experimental approach, which includes plant determination, preparation of infusion, and phytochemical screening. The infusion process is carried out to extract active compounds using water as a solvent under controlled conditions. The phytochemical screening is conducted to qualitatively detect the presence of various bioactive compounds. The results of the screening on three formulations (F1, F2, and F3) show that all infusa preparations contain several important secondary metabolites, including alkaloids, flavonoids, saponins, tannins, and terpenoids. These findings indicate that the combination of the three herbal plants has the potential to provide enhanced pharmacological effects due to the diversity of active compounds present in the formulation.